2D DIGE Does Not Reveal all: A Scotopic Report Suggests Differential Expression of a Single “Calponin Family Member” Protein for Tetany of Sphincters! - Chaudhury, Arun (Frontiers in Medicine, 2015)
Using 2D differential gel electrophoresis (DIGE) and MS (mass spectrometry), a recent report by Rattan and Ali (2015) compared proteome expression between tonically contracted sphincteric smooth muscles of the internal anal sphincter (IAS), in comparison to the adjacent rectum (RSM, rectal smooth muscles) that contracts in a phasic fashion. The study showed the differential expression of a single 23 kDa protein SM22, which was 1.87 fold overexpressed in RSM in comparison to IAS. Earlier studies have shown differences in expression of different proteins like Rho-associated protein kinase II (ROCKII), myosin light chain kinase (MLCK), myosin phosphatase (MYP) and protein kinase C (PKC) between IAS and RSM. The currently employed methods, despite its high-throughput potential, failed to identify these well-characterized differences between phasic and tonic muscles. This calls into question the fidelity and validatory potential of the otherwise powerful technology of 2D DIGE/MS. These discrepancies, when redressed in future studies, will evolve this recent report as an important baseline study of “sphincter proteome”. Proteomics techniques are currently underutilized in examining pathophysiology of hypertensive/hypotensive disorders